Harmony Muslim Family Education in The Digital Era: An Islamic Perspective - Sholeh, Muhammad Muhtar Arifin; Waston, W; Nugroho, Kharis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Family is a very important part of a Muslim's life. Therefore, how to educate Muslim family members is mandatory, so that it becomes a harmonious family (Sakinah, Mawaddah, and Rahmah - samara). The main purpose of this study is to draw on how to educate Muslim family members in the digital era and how to prepare a harmonious Muslim family, according to the Islamic perspective. The study is very important to recognize since every person has a family and wants to make it harmonious. Islam gives instructions on how to educate family members, especially in today's digital age, as Luqmanul Hakim's advice in the Qur'an surah Luqman verses 12-19. The hadith (sayings of the Prophet Muhammad) also gives many instructions. Luqmanul Hakim gave the following instructions: Thanksgiving (verse 12), Aqidah Tauhid (verse 13), Dedication to the parents (vv. 14-15), Responsibility (verse 16), Upholding Prayer (Shalat) (verse 17), Amar ma’ruf Nahi Munkar (verse 17), and Akhlaqul Karimah (verse 18-19). In addition to paying attention to Luqmanul Hakim's advice above to educate Muslim family members in the digital age, some traits and attitudes that must also be considered are honesty (shidiq), trustworthiness (Amanah), Patience (Handling of angry passions) - ash-shabr, humble (tawadhu’), firm stance (istiqomah), and No Ghibah and Non-Slander.